HELMENTHIC INFESTATION PRESENTING AS CHOLECYSTITIS - Afridi, Shah Jehan; Shah, S. Humayun; Sultan, S. (Journal of Ayub Medical College Abbottabad, 1991)
Helminthic infestation is a common health problem in our country. Its prevalence depends on climate, socio-economic, unhygienic conditions and basic health education. Several surveys regarding the incidence of worm infestation in various countries of the world are available. In Bangladesh slum, over 80% of the population have one or more parasites.1 In some parts of India, Ascaris infection has been reported upto 95%.2 In Pakistan the prevalence of parasites in diarrheal disease was found to be 71%, with a high rate of Giardia lambilia.3 Many of the worms have been associated with malnutrition. Beside malnutrition a variety of other problems have been reported as a result of worm infestation. These include recurrent diarrhoea and vomiting, malabsorption, appendicitis, respiratory infections, intestinal obstruction and hepatomegaly. We present two case reports which were admitted for obstructive jaundice and after investigation they were diagnosed as infestation by Ascaris lambricoides obstructing bill duct.